Flying at night : poems 1965-1985 - Kooser, Ted. (Pittsburgh : University of Pittsburgh Press, 2005)
Named U.S. Poet Laureate for 2004-2006, Ted Kooser is one of America's masters of the short metaphorical poem. Dana Gioia has remarked that Kooser has written more perfect poems than any poet of his generation. In Flying at Night: Poems 1965-1985, Kooser has selected poems from two of his earlier works, Sure Signs and One World at a Time (1985). Taken together or read one at a time, these poems clearly show why William Cole, writing in the Saturday Review, called Ted Kooser ""a wonderful poet, "" and why Peter Stitt, writing in the Georgia Review, proclaimed him ""a skilled and cunning writer
Furnace -- West window -- Boarding house -- A letter from Aunt Belle -- At the bait stand -- The tattooed lady -- A death at the office -- There is always a little wind -- The Widow Lester -- Houses at the edge of town -- The old woman -- A place in Kansas -- Tom Ball's barn -- My grandfather dying -- The Red Wing Church -- Highway 30 -- Birthday -- The failed suicide -- The goldfish floats to the top of his life -- They had torn off my face at the office -- Year's end -- New Year's Day -- Walking to work -- Sunday morning -- [pt. 2]. One world at a time -- Flying at night -- A fencerow in early March -- Just now -- A birthday card -- In the basement of the Goodwill Store -- Camera -- A room in the past -- In January, 1962 -- Tillage marks -- A child's grave marker -- Father -- At midnight -- Central -- The fan in the window -- Myrtle -- Daddy longlegs -- Good-bye -- The giant slide -- A roadside shrine in Kansas -- Decoration day -- A Monday in May -- A buffalo skull -- Laundry -- The mouse -- Ladder -- Walking at noon near the Burlington Depot in Lincoln, Nebraska -- A patch of sunlight -- Carp -- At the center -- A sunset -- The ride -- At nightfall -- At the office early -- Cleaning a bass -- An empty shotgun shell -- A quarter moon just before dawn -- A letter -- Latvian neighborhood -- The Voyager II satellite -- The witness -- As the President spoke -- The pitch -- The sigh -- The onion woman -- Hobo jungle -- An August night -- The urine specimen -- Geronimo's mirror -- Porch swing in September.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Poetry; Poetics; Poésie.; Poétique.; poetry; LITERARY CRITICISM -- Poetry; POETRY -- American -- General; Poetics; Poetry